Laparoscopic transdiaphragmatic pericardial fenestration in palliative care: how I do it. Issue 1 (2nd January 2021) - De Haes, Femke; Zimmerman, D. D. E.; Özmen, Mustafa; Göttgens, Kevin W. A.; Langenhoff, Barbara S.
Abstract: Background: The optimal therapeutic strategy for drainage of malignant pericardial effusion is not yet determined. Several techniques are described, with different benefits and disadvantages. The literature suggests that surgical drainage of pericardial effusions has less effusion recurrence; however, randomized controlled trials are not available. Due to the nature of the disease, quality of life should always be considered while making treatment decisions. Methods: A retrospective analysis of all consecutive patients from November 2016 until June 2019 of our institution in the Netherlands was performed. All patients underwent laparoscopic pericardial fenestration after echocardiography and request for operative treatment by the cardiologist. The same operation technique was performed in every case. Results: Four out of five of our patients needed pericardial fenestration because of oncological diseases. No hemodynamically instability was noted during this fast technique, achieving direct relief of symptoms. No treatment-related morbidity or mortality, nor the need for re-intervention was encountered. We compared the outcome of our five patients with the existing evidence in the literature. Conclusions: In this article, we highlight the laparoscopic transdiaphragmatic pericardial fenestration as a treatment of preference in a non-acute palliative setting. This laparoscopic approach is safe, and can be a valuable alternative among the other well-known approaches.